2010
DOI: 10.1371/journal.pntd.0000878
|View full text |Cite
|
Sign up to set email alerts
|

Arbovirus Detection in Insect Vectors by Rapid, High-Throughput Pyrosequencing

Abstract: BackgroundDespite the global threat caused by arthropod-borne viruses, there is not an efficient method for screening vector populations to detect novel viral sequences. Current viral detection and surveillance methods based on culture can be costly and time consuming and are predicated on prior knowledge of the etiologic agent, as they rely on specific oligonucleotide primers or antibodies. Therefore, these techniques may be unsuitable for situations when the causative agent of an outbreak is unknown.Methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 34 publications
1
59
0
Order By: Relevance
“…1 Recent studies have shown that the microbiota of mosquitoes can affect their ability to become infected with and to vector certain pathogens. [2][3][4][5] There is a growing realization that mosquito populations are naturally infected with a wide range of bacteria, 6,7 fungi, 8 and viruses [9][10][11][12][13][14][15] ; and this recognition has raised interest in the potential effects of these microbes on mosquito ecology and on pathogen transmission.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent studies have shown that the microbiota of mosquitoes can affect their ability to become infected with and to vector certain pathogens. [2][3][4][5] There is a growing realization that mosquito populations are naturally infected with a wide range of bacteria, 6,7 fungi, 8 and viruses [9][10][11][12][13][14][15] ; and this recognition has raised interest in the potential effects of these microbes on mosquito ecology and on pathogen transmission.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, efforts have been made to use NGS-based approaches, in particular pyrosequencing, for obtaining genetic data from different viral pathogens, such as HIV; avian leukosis virus; lyssaviruses; enteric viruses, and few arboviruses, including DENV-1 and phleboviruses (Victoria et al, 2009;Bimber et al, 2010;Bishop-Lilly et al, 2010;Day et al, 2010;Hedskog et al, 2010;De Wolf et al, 2011;Schinazi et al, 2011;Abbate et al, 2011;De Benedictis et al, 2011;Palacios et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Methods for removal of host nucleic acid have mostly focused on rRNA (O'Neil, Glowatz, & Schlumpberger, 2013). In the case of RNA-seq studies or detection of RNA viruses, these methods improve coverage of microbial genomes (Bishop-Lilly et al, 2010). However, especially in the case of clinical samples, often host nucleic acid is genomic DNA.…”
Section: Where Future Efforts Should Focusmentioning
confidence: 99%